Two new Oriental genera of Cephenniini (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Two new genera are proposed, Foveomicrus gen. n. (type species Foveomicrus indicus sp. n.) and Indomicrus gen. n. (type species Indomicrus chera sp. n.), for south Indian species of Cephenniini. The new taxa are classified as members of the ‘Cephennomicrus group’ of genera, characterized, among others, by a short and broad, button-like maxillary palpomere IV. Relationships of Foveomicrus and Indomicrus are discussed, and an updated identification key to world genera of Cephenniini is presented.